Diarylheptanoids of Alpinia Species (Zingiberaceae): A Review of Phytochemistry and Pharmacological Potential - Wan Salleh, Wan Mohd Nuzul Hakimi (Journal of Pharmacy, 2026)
Introduction: Diarylheptanoids, a distinctive class of secondary metabolites characterized by a 1,7-diphenylheptane backbone, are widely distributed in Alpinia species (Zingiberaceae) and have attracted considerable scientific interest due to their diverse structural variations and promising bioactivities. Methods: This review summarizes the current state of knowledge on diarylheptanoids isolated from Alpinia, focusing on their phytochemical diversity, structural classifications, and biosynthetic considerations. Results: To date, numerous diarylheptanoids, including linear, cyclic, and rearranged derivatives, have been identified, reflecting the remarkable chemodiversity of this genus. Pharmacological studies reveal that these compounds exhibit a wide spectrum of biological activities, notably anti-inflammatory, antioxidant, anticancer, antimicrobial, antidiabetic, and neuroprotective properties, supporting their therapeutic potential. Special emphasis is placed on structure–activity relationships, which provide insights into the molecular features governing their bioactivity. Conclusion: The review highlights research gaps, such as limited mechanistic studies and in vivo validations, and suggests future directions for drug discovery and development from Alpinia-derived diarylheptanoids. By integrating phytochemical and pharmacological perspectives, this work provides a comprehensive resource for researchers exploring natural product-based therapeutics.